Rebuilding peace: The role of elections in Sierra Leone's post-conflict transformation (2002–2018) - Ofordi, Joy Amarachi; Aleyomi, Paul Timileyin (Yayasan Mitra Persada Nusantara, 2025)
This study explores the impact of post-conflict elections in Sierra Leone from 2002 to 2018, with a critical focus on whether these electoral processes have truly furthered sustainable peace, inclusive development, and democratic consolidation. Elections are frequently presented as crucial instruments for post-war recovery—especially through the lens of the liberal peacebuilding framework—but their long-term effectiveness within fragile societies remains contentious. The research aims to move beyond the surface-level restoration of political order by assessing the deeper, more enduring consequences of electoral interventions. Employing a qualitative case study approach, the study analyses data from elections, government documentation, and existing scholarly literature to evaluate the political, social, and economic effects of five post-conflict electoral cycles in Sierra Leone. Situated within the broader context of liberal peace theory—which places particular emphasis on democratization through elections—the work also engages with critical perspectives that caution against the risks associated with premature or externally imposed democratic practices in post-war environments. The findings indicate that although elections in Sierra Leone did succeed in re-establishing state legitimacy and averting a return to armed conflict, significant core problems persist. Issues such as youth marginalization, pronounced regional inequalities, and entrenched elite dominance have remained largely unaddressed by electoral processes alone. These structural barriers continue to obstruct wider goals of peacebuilding and development. In conclusion, the study argues that electoral processes, while necessary, are by themselves insufficient for realizing substantive transformation in post-conflict contexts. It advocates for a more sequenced, context-sensitive strategy—one that effectively integrates electoral reforms with measures for socio-economic inclusion and institutional strengthening. For lasting peace and development in post-war societies, a comprehensive approach to peacebuilding that goes well beyond the mere act of voting is essential.